SGLT-2 Inhibitors in Development for Type 2 Diabetes Treatment (The Review of Diabetic Studies, 2023)
The prevalence of type 2 diabetes is increasing worldwide. The majority of currently available glucose-lowering agents work via insulin-dependent mechanisms and have significant limitations. Hence, there is a need for newer treatments utilizing novel therapeutic targets. Drugs which inhibit the sodium glucose cotransporter in the renal tubules (SGLT-2 inhibitors), represent a novel class of drugs under development. By inhibiting SGLT-2, they promote increased renal glucose excretion and thereby calorie loss with improved glycemic control and weight loss. Dapagliflozin is most advanced in development of this new drug class and currently undergoing phase 3 trials. In addition to its glucose lowering effect, dapagliflozin appears to have favorable impacts on weight and blood pressure, with low risk of hypoglycemia. However, as with all new treatments, long-term safety is an issue. Clinical trials showed increased risk of genital and possibly urinary infections with dapgliflozin. Furthermore, concerns have arisen regarding a possible increased incidence of breast and bladder cancer in patients on dapagliflozin. However, it needs further investigation to confirm or refute whether these concerns are concrete.